2017
DOI: 10.1371/journal.pntd.0006120
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Giardia intestinalis secretome during interaction with human intestinal epithelial cells: The impact on host cells

Abstract: BackgroundGiardia intestinalis is a non-invasive protozoan parasite that causes giardiasis in humans, the most common form of parasite-induced diarrhea. Disease mechanisms are not completely defined and very few virulence factors are known.MethodologyTo identify putative virulence factors and elucidate mechanistic pathways leading to disease, we have used proteomics to identify the major excretory-secretory products (ESPs) when Giardia trophozoites of WB and GS isolates (assemblages A and B, respectively) inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
111
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(129 citation statements)
references
References 115 publications
7
111
0
2
Order By: Relevance
“…The stefins are mainly intracellular inhibitors but they were found in body fluids or in the excretory-secretory products (ESPs) of trematodes [48][49][50]. We confirmed robust expression of G. intestinalis cystatin in trophozoites and encysting trophozoites, as previously indicated by separate studies under different stress conditions, differentiation and host-parasite interactions [3,32,34,35,51]. In one of the studies equally robust expression of cystatin comparable to trophozoites cultures was shown in the mouse intestine, further highlighting the potentially important role of cystatin during infection [35].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The stefins are mainly intracellular inhibitors but they were found in body fluids or in the excretory-secretory products (ESPs) of trematodes [48][49][50]. We confirmed robust expression of G. intestinalis cystatin in trophozoites and encysting trophozoites, as previously indicated by separate studies under different stress conditions, differentiation and host-parasite interactions [3,32,34,35,51]. In one of the studies equally robust expression of cystatin comparable to trophozoites cultures was shown in the mouse intestine, further highlighting the potentially important role of cystatin during infection [35].…”
Section: Discussionsupporting
confidence: 86%
“…B). We further tested the inhibition capacity of G. intestinalis cystatin to human cathepsin B, which is highly expressed in human intestine and abundant in the secretome of intestinal cell lines during interaction with Giardia trophozoites (https://www.proteinatlas.org/ENSG00000164733-CTSB/tissue, ), and the inhibiting activity was weaker ( K i of 79.88 ± 16.76 n m ) as compared to papain (Fig. C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…EVs from Giardia have previously been studied in host-pathogen interactions through proteomic analysis of excretory-secretory products (ESP), including EVs of axenic cultures and cultures of trophozoite interacting with mammalian cells, where proteins related to metabolism were found, without signal peptides on EVs (Ma’ayeh et al 2017). In addition, ESP containing cleavage activity trough cysteine proteases have been identified (de la Mora-de la Mora et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Its G. intestinalis homolog is up-regulated and secreted during interactions with human 480 intestinal epithelial cells 8 and it cleaves chemokines, tight junction proteins and 481 defensins 12,75 . Thus, this is most likely also an important virulence factor in G. muris.…”
Section: Recombination 460mentioning
confidence: 99%